Clinical exome sequencing facilitates the understanding of genetic heterogeneity in Leber congenital amaurosis patients with variable phenotype in southern India - Sriee Viswarubhiny; Rupa Anjanamurthy; Ayyasamy Vanniarajan; Devarajan Bharanidharan; Vijayalakshmi Perumalsamy; Periasamy Sundaresan (Eye and Vision, 2021)
Abstract Background Leber congenital amaurosis (LCA), primarily characterized by retinal degeneration is the most severe form of inherited retinal dystrophy (IRD) responsible for congenital blindness. The presence of phenotypic heterogeneity makes the diagnosis of LCA challenging, especially in the absence of pronounced disease pathognomonic, yet it can be well comprehended by employing molecular diagnosis. Therefore, the present study aimed to reveal the causative mutations in ten LCA patients with variable phenotypes using clinical exome sequencing (CES). Methods CES was performed in ten unrelated LCA patients. Ophthalmic information and family history of all patients were obtained to make a meaningful interpretation. The clinical exome data was analyzed and prioritized using a bioinformatics pipeline to identify mutations, which was further validated by Sanger sequencing. Segregation analysis was also performed on available family members. Results CES led to the identification of causative mutations in nine LCA patients. Seven patients harbored a mutation in six LCA candidate genes, including RPE65, LCA5 (n = 2), CRX, PRPH2, CEP290, and ALMS1, while two patients possess a mutation in IFT80 and RP1, known to cause other diseases. Three novel mutations in LCA5 (c.1823del), CRX (c.848del) and CEP290 (c.2483G > T) were identified. The current study reports for the first time, a mutation in PRPH2, CEP290, and ALMS1 from the Indian population. Additionally, we observed a novel association of LCA phenotype with IFT80 known to cause Jeune syndrome. Based on the genetic finding, the patient AS09, who harbored a mutation in the RP1 gene, was re-diagnosed with early-onset retinitis pigmentosa. Conclusion In conclusion, the results underline the importance of CES in clinically diagnosed LCA patients with variable phenotypes. The correlation between mutations in candidate genes and clinical phenotypes, helps to refine the clinical diagnosis. However, molecular evaluation with a larger cohort of LCA patients is needed for better understanding of the mutational spectrum in southern India.